Methodological Features Of Teaching Foreign Languages - Kodirova Fazilat (Genius Journals, 2023)
The article discusses methods of teaching a foreign language, ways to accelerate it, and the general process of mastering a new language. The use of basic approaches and their implementation in the educational process. The main types of activities and requirements in the relationship between a teacher and a student using a communicative approach are presented.
Keywords: method; translation method; comparative method; direct method